Reading Between the Lines of Online Course Evaluations: Predictable Actions that Improve Student Perceptions of Teaching Effectiveness and Course Value - Stephanie J Jones (Online Learning, 2012)
Students continue to demand and enroll in online courses, but are not always satisfied with their experiences. The purpose of this study was to determine if students’ responses to evaluations for online courses could be used to predict faculty actions that could lead to improved evaluation scores in teaching effectiveness and overall course value. Controversy continues to exist over the validity of student evaluations to measure faculty effectiveness and overall course quality. Faculty seldom utilize the collected data for the improvement of teaching. Results indicate that stimulation of learning had the most effect on perceptions of teaching effectiveness and useful and relevant assignments had the highest correlation to overall course value.